Studi Kasus Pada Pasien Dengan Hipertensi Melalui Penerapan Rebusan Daun Sambung Nyawa: Studi Kasus Pada Pasien Dengan Hipertensi Melalui Penerapan Rebusan Daun Sambung Nyawa - Isna Aglusi Badri (Akper Kesdam I/Bukit Barisan Padang, 2021)
Hypertension is the number 1 cause of death in the world and the third largest cause of death in Indonesia with a percentage of 6.7% after stroke and heart disease. The purpose of this scientific paper is to provide a comprehensive overview of nursing care for elderly people managed with hypertension. The method used in papers is a case study based on the stages of nursing care including assessment, diagnosis, intervention, implementation and evaluation of nursing. The results of the study showed that the elderly complained, the head hurt, the neck was tense, the client looked pale, the skin felt cold, so that the nursing diagnosis that appeared was ineffective peripheral perfusion associated with hypertension, the client complained of headaches, pain spreads to the neck, the pain disappeared and arose a pain scale. 5 diagnoses that emerged were acute pain associated with increased cerebral vascular pressure, and the client complained of numb legs, not being able to stand too long and walking long distances, having fallen ± 3 months ago the diagnosis that appeared was the risk of falling associated with a history of falls, neuropathy. The end of providing nursing care by providing boiled water of gynura procumbens once a day (150 ml) during the day for 7 days can reduce blood pressure in elderly people with hypertension so that it can be used as an alternative non-pharmacological treatment that has no effect. side that is detrimental, and easy to get. Suggestions for the elderly who have hypertension can apply boiled water of gynura procumbens at home because it is easy to do by yourself.